Karakter Diplomasi Publik Indonesia terhadap Malaysia - Iva Rachmawati (Universitas Muhammadiyah Yogyakarta, 2017)
Public diplomacy, as an effort to maintain the system of inter-state relations and also its existence in the international environment, refers to the communicative activities of the state as well as the domestic public to the public outside the state. Public diplomacy then becomes a supportive tool for maintaining inter-state relations and avoiding conflicts arising between countries. However, in Indonesia-Malaysia relations, the practice of public diplomacy tends to lead to negative actions in influencing relations. This article shows that negative Indonesian public diplomacy towards Malaysia has been influenced by distinctive characters, reactive and inferior. Those characters were formed by historical frame on collective memory which collide Malaysian NEP impact. As a result, public diplomacy does not exist as a bridge to maintain relationships positively but rather tends to be practised through negative communication forms. This article is a result of qualitative research methods based on interviews and literature studies. Diplomasi publik, sebagai upaya untuk memelihara sistem relasi antar negara dan juga keberadaannya dalam lingkungan internasional yang merujuk pada aktfitas komunikatif publik domestik suatu negara terhadap publik di luar negara. Diplomasi publik kemudian menjadi alat yang suportif untuk menjaga relasi antar negara dan menghindarkan negara dari konflik akibat persoalan yang muncul antar negara. Namun, pada relasi Indonesia-Malaysia, praktik diplomasi publik cenderung mengarah pada tindakan-tindakan yang negatif dalam memengaruhi relasi. Artikel ini menunjukkan bahwa praktik-praktik diplomasi publik Indonesia terhadap Malaysia yang negatif tersebut dipengaruhi oleh karakter yang khas, yaitu karakter reaktif dan inferior. Karakter tersebut terbentuk oleh bingkai sejarah pada memori kolektif yang bertemu dengan dampak NEP Malaysia. Akibatnya, diplomasi publik tidak hadir sebagai jembatan untuk memelihara relasi secara positif melainkan cenderung dipraktikkan melalui bentuk-bentuk komunikasi yang negatif. Artikel ini merupakan hasil riset yang dilakukan dengan metode kualitatif berdasar pada wawancara dan studi literatur.